Establishment of a District Metered Area (DMA) and Water Loss Analysis in Pilang Setrayasa Cirebon - M Rifki; Ohan Farhan (Riviera Publishing, 2026)
Based on customer complaints in the Pilang–Sertayasa area, several issues related to suboptimal water pressure were identified. These issues were attributed to high levels of water loss. This study aimed to determine the level of water loss through the establishment of District Metered Areas (DMA). A descriptive-quantitative research design was employed to evaluate the level of Non-Revenue Water (NRW) through the implementation of a District Metered Area (DMA) in Pilang–Sertayasa, involving a study population of 217 active customers. The instrument used to assess water loss was the DMA method. Water loss analysis was conducted using data loggers, with the collected data analyzed through step-test calculations. The findings revealed that the water loss level, or Non-Revenue Water (NRW), within the Pilang–Sertayasa DMA reached 48.43%. The step-test analysis indicated that Step 1 (0.0125 dQ/Dsr), Step 6 (0.0206 dQ/Dsr), and Step 7 (0.0437 dQ/Dsr) were categorized as high-loss areas. Therefore, immediate interventions, such as leak detection and further evaluation, were required for these steps to reduce water losses and improve distribution system efficiency.